UJI KINERJA DAN KELAYAKAN FINANSIAL PENGERING PATI SAGU TIPE PNEUMATIC CONVEYING RING DRYER - Abadi Jading; Paulus Payung; Eduard Fransisco Tethool (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Sago starch drying in remote areas or difficult to reach transportation requires artificial dryers to increase the quantity and quality of the dry sago starch. The purpose of this study was to test performance, and analyze the economic value of biomass powered pneumatic conveying ring dryer (PCRD) for drying sago starch for small scale commercial. This research was conducted in two stages, namely performance testing and financial analysis. Small scale (mini) PCRD has been created for drying sago starch with a capacity of 160 kg of dry sago starch per day. The resulting moisture content varies according to variations in temperature and initial moisture content of sago starch and has met the Indonesia National Standard (SNI) No. 3729 regarding the maximum water content of sago starch (13%), except at temperature variations of 50oC and 75oC with an initial moisture content of 41% that did not meet the SNI, which was greater than 13% (14.27% and 13.23%). The drying efficiency varies between 7.339% to 9.689%. Likewise, the yield of dry sago starch that was produced varied between 65% and 73%. PCRD is very feasible to be developed into a commercial scale sago starch dryer with a Pay back value of 2.66 years to return the initial capital of Rp. 186,879,200. Keywords: drying, financial analysis, PCRD, sago starch